Ultra-processed Foods Consumption Increases the Risk of Hypertension in Adults: A Systematic Review and Meta-analysis - Wang, Mei; Du, Xinyi; Huang, Wei; Xu, Yong (American journal of hypertension, 2022)
Effect of ultra-processed foods (UPFs) consumption on health has attracted widespread attention in recent years. However, the relationship between UPFs consumption and hypertension is unclear. This meta-analysis was conducted to analyze the above association. We systematically searched PubMed, Embase, and Cochrane Library for all relevant studies published up to 31 January 2022 without language limitation. The random-effects model was selected to pool the effect sizes and 95% confidence intervals (CIs). Nine observational studies involving 111,594 participants were included. Results from this meta-analysis showed that higher UPFs consumption significantly increased the risk of hypertension (odds ratio: 1.23; 95% CI: 1.11, 1.37; P = 0.034). Furthermore, analyses were performed based on gender, study design, exposure assessment, outcome assessment, body mass index, energy intake, and physical activity, which suggested that the results remained statistically significant. Our findings suggested that UPFs might have detrimental effects on the incidence of hypertension in the general population. Although current evidence is limited, it cannot be denied that reducing consumption of UPFs may contribute to decrease the risk of chronic noncommunicable diseases.